A comparison of clinical, biochemical, and histological characteristics as well as evaluation of outcomes of patient with mesangiovapillary glomerulonephritis (MCGN) in HIV positive and negative patients at a tertiary hospital in Cape Town, South Africa - Sorathia, Shaheed Salim Gulamali (Department of Medicine, 2023)
Background & Aim Mesangiocapillary glomerulonephritis (MCGN) is a common histological pattern of glomerular injury in developing countries. South Africa has the highest proportion of people living with HIV (PWH) and the co-existence of MCGN and HIV may affect kidney prognosis. The aim of this study was to compare the clinical and biochemical features between PWH and HIV-negative individuals with a diagnosis of MCGN and to review kidney function and survival. Materials and Methods A retrospective study was conducted in patients with a biopsy diagnosis of MCGN between January 2010 and December 2017. The following data were collected: age, sex, use of illicit drugs, date of initiation of antiretroviral therapy (ART), blood pressure, presence of oedema, need for kidney replacement therapy, HIV status, CD4 and viral load. Secondary causes were excluded. Kidney outcomes [(serum creatinine, estimated glomerular filtration rate (eGFR), urine protein creatinine ratio (uPCR)] were assessed at 6, 12 and 24 months post biopsy. The composite outcome was defined as a 40% decline in eGFR, progression to end stage kidney disease or death. Results: The study included 116 participants: 27 (23%) were PWH, 89 (77%) were HIV-negative. The median age was 33 years. There were more males in the HIV-negative group [63/89 (71%)]. Oedema was more common in HIV-negative patients [66/86 (77%), p=0.011]. Haemoglobin and albumin were lower in PWH [9.1g/dL vs 11.2 g/dL (p=0.053) and 20 g/L vs 27 g/L, (p=0.053), respectively]. Baseline creatinine, eGFR and uPCR were not different between the groups. However, at 6 and 12 months the creatinine was higher in PWH: 137 μmol/L compared to 97 μmol/L (p=0.028) and 125 μmol/L compared to 87 μmol/L(p=0.023), respectively. uPCR was higher in PWH at 6 and 12 months: 0.63 g/mmol vs 0.075 g/mmol, (p=0.002) and 0.28 g/mmol vs 0.028 g/mmol, (p=0.022), respectively. The composite endpoint was not different between the two groups in the first three years of follow-up.